Modification of microstructure, hardness, and wear characteristics of an automotive-grade Al-Si alloy after friction stir processing. Issue 23 (2nd December 2021) - Charandabi, Fatemeh Kaffash; Jafarian, Hamid Reza; Mahdavi, Soheil; Javaheri, Vahid; Heidarzadeh, Akbar
Abstract: The surface structure and properties of a cast piston alloy were improved after friction stir processing at a tool rotation rate of 710 rpm and tool traverse speed of 100 mm/min. The microstructure of the base and processed materials were characterized using an optical microscope, and a scanning electron microscopy equipped with energy dispersive spectroscopy. Vickers hardness and wear tests were conducted to evaluate the mechanical properties. The results showed that friction stir processing eliminated the dendritic structure, porosities, and segregation of the base material. Besides, it caused fragmentation and uniform redistribution of the large Si, Fe, and Cu-rich components in the aluminum alloy matrix. The hardness of piston alloy was increased from 47 to 68 HV. Moreover, the wear properties were improved so that the amount of volume loss decreased from 0.37 to 0.22 mm 3, and the friction coefficient from 0.52 to 0.44. The fragmentation mechanism of intermetallic compounds and the wear mechanism of the base and processed materials are discussed.